2008
DOI: 10.1038/nmat2301
|View full text |Cite
|
Sign up to set email alerts
|

Insight into silicate-glass corrosion mechanisms

Abstract: The remarkable chemical durability of silicate glass makes it suitable for a wide range of applications. The slowdown of the aqueous glass corrosion kinetics that is frequently observed at long time is generally attributed to chemical affinity effects (saturation of the solution with respect to silica). Here, we demonstrate a new mechanism and highlight the impact of morphological transformations in the alteration layer on the leaching kinetics. A direct correlation between structure and reactivity is revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
413
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(449 citation statements)
references
References 44 publications
29
413
2
5
Order By: Relevance
“…[1][2][3][4][5][6][7] Hydration degrades the surface of the glass [7][8][9] and may affect glass strength due to interaction of hydrated layer with strength controlling defects. 9,10 Although, the phenomenon of glass surface hydration is still not fully understood, most researchers agree that hydration involves several competing processes, the most significant of which are leaching (often referred to as ion exchange) and network dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Hydration degrades the surface of the glass [7][8][9] and may affect glass strength due to interaction of hydrated layer with strength controlling defects. 9,10 Although, the phenomenon of glass surface hydration is still not fully understood, most researchers agree that hydration involves several competing processes, the most significant of which are leaching (often referred to as ion exchange) and network dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…The slower degradation glass rates observed in the natural system result from a number of differences between those systems and glass studies in the laboratory including (a) dissolution mechanisms (Hamilton et al 2001) and (b) glass reactive surface area (Wolf-Boenisch et al 2004). Each of these aspects of the degradation are affected by coupled feedback processes resulting during glass degradation due to formation of diffusion pathways through intermediate phases (e.g., gel layer), which may also develop to isolate fresh glass surfaces from contact with the bulk fluid (Cailleteau et al 2008;Verney-Carron 2010).…”
Section: Repository Settings -Why and When Glass Waste Form Dissolutimentioning
confidence: 99%
“…(after Frugier et al 2008). Experimental studies of mineral dissolution kinetics (e.g., Hamilton et al 2001;Hellmann and Tisserand 2006;Yang and Steefel 2008;Pierce et al 2010) and of the related process of glass degradation (e.g., Strachan and Croak 2000;Advocet et al 2001;Wolf-Boenisch et al 2004;Pierce et al 2006;Cailleteau et al 2008) have provided data to show that there is a complex coupled feedback process that changes glass degradation from simple far-from equilibrium dissolution kinetics at the start to slower degradation controlled in part by diffusion processes in gel and secondary phase layer(s) in which the reaction solution has a modified composition near the surface (i.e., the reactive interface) of fresh glass (see Grambow 2006;Van Iseghem et al 2007). In these cases the compositional gradients of the solution need to be taken into account and evaluated on a smaller scale than the bulk solution (Li et al 2008) and the appropriate approach to developing models of this coupled reaction and transport system is in general a reactive transport methodology (e.g., Steefel et al 2005).…”
Section: Current Understanding and Gap Identificationmentioning
confidence: 99%
“…All these studies seem to give much lower rates of dissolution compared to these invivo results. Generally, the corrosion or dissolution mechanism for silica is the formation of a hydrated surface that dissolves to form aqueous Si(OH) 4 , although the specific mechanism is thought to include several coupled mechanisms: hydration, hydrolysis of covalent network, and exchange between alkali ions and protons in solution involving protonation-deprotonation reactions [12], [14], [23], [24], [29]. For instance, the buildup of silica in the test solution can ultimately saturate the solution with silica, and slow dissolution process by up to a factor of 1000.…”
mentioning
confidence: 99%
“…Correspondingly, the effect of surface area to solution volume ratio on dissolution rate has been known for over 30 years [17]. Recently, however, Cilleteau et al, have reported that in some cases this sharp drop in glass corrosion may not be associated with the solution saturation effect but instead a result of densification of the outer layers of the surface film [29]. In addition, there is recent research that indicates the presence of certain cations and organic compounds will also affect the dissolution rates [24], [25].…”
mentioning
confidence: 99%